Fear of stigmatization prevents individuals from claiming benefits - Jana Friedrichsen; Renke Schmacker (DIW Weekly Report, 2019)
The desire to avoid the shame of being dependent on government aid is often cited as a cause of low welfare take-up rates. In contrast to other obstacles, such as transaction costs or a lack of information, little empirical research has been conducted on how stigma affects social benefits take-up. In this Weekly Report, a controlled laboratory experiment is presented whose results support the following hypothesis: potential recipients fear being perceived as low-skilled (ability stigma) or willing to live off others (free-rider stigma). Hence, they choose to forego a beneficial transfer if it must be claimed publicly. The results indicate that increasing the discreetness of the application and payout processes would help dismantle the stigma and thus increase the welfare take-up rate.
Keywords: C91; D03; H31; I38; 330; Stigma; Signaling; Non-take-up; Welfare program